Acquired Digital Fibrokeratoma. Issue 3 (March 2015) - Yu, Deborah; Morgan, Raymond F.
<x xml:space="preserve">Abstract</x> Abstract Acquired digital fibrokeratomas are benign, rare tumors that develop most commonly on the fingers. They can have an appearance of a rudimentary supernumerary digit or be misdiagnosed as a more common condition, such as verruca vulgaris. There are no case reports described in the plastic surgery literature. We are reporting a case that presented to our institution recently.